Effect of broad-spectrum parenteral antibiotics on "colonization resistance" of intestinal microflora of humans. - Barza, M (1987)
Studies with animals have shown that the normal intestinal microflora protects against colonization by new strains ("colonization resistance") and that this protective effect may be related to the anaerobic component of the microflora. However, colonization resistance has not been shown in humans. We administered cefoxitin, piperacillin, cefoperazone, and aztreonam intravenously to healthy subjects for 9 days and monitored the acquisition of new isolates in the fecal flora. Seven of sixteen antibiotic-treated subjects but none of four untreated controls became colonized by gram-negative bacilli. However, there was no correlation between colonization and the particular drug given or the extent of suppression of anaerobes or of any other component of the fecal microflora. Cefoxitin and piperacillin were associated with the greatest increases in the numbers of drug-resistant bacteria and in fecal beta-lactamase content. The results of this study support the concept that colonization resistance occurs in humans and is diminished by antibiotic administration but fail to support the hypothesis that resistance is related to the anaerobic microflora.